Odd, outsized, and obscure: Sarcophaga (Hadroxena) karakoncolos sp. n. (Diptera: Sarcophagidae) from Turkey - Whitmore, Daniel; Buenaventura, Eliana; Pape, Thomas (Zootaxa, 2018)
A new species of flesh fly, Sarcophaga karakoncolos sp. n., is described based on a single adult male from Turkey (Isparta Province, Anatolia), characterised by its very large size (almost 22mm in body length) and by a unique combination of morphological features. These, together with available molecular data, do not support inclusion of the new species in any of the currently recognised subgenera of Sarcophaga, and it is placed in a new subgenus, Hadroxena subg. n.